2015
DOI: 10.1021/jf503948p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Timing and Severity of Salinity Stress on Rice (Oryza sativa L.) Yield, Grain Composition, and Starch Functionality

Abstract: TitleEffects of timing and severity of salinity stress on rice (Oryza sativa L.) yield, grain composition, and starch functionality ABSTRACT: The aim of this work was to examine agronomic, compositional, and functional changes in rice (Oryza sativa L. cv. Nipponbare) grains from plants grown under low-to-moderate salinity stress in the greenhouse. Plants were grown in sodium chloride-containing soil (2 or 4 dS/m 2 electrical conductivity), which was imposed 4-weeks after transplant (called Seedling EC2 and EC4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 51 publications
(174 reference statements)
6
64
3
Order By: Relevance
“…For instance, ozone (O 3 ) (Piikki et al 2008 ; Zheng et al 2013 ) and heat (Farooq et al 2011 ) stresses have been shown to increase the GPC in wheat, while the study conducted by Fuhrer et al ( 1990 ) revealed that O 3 stress decreases the GSC. In rice, the GSC decreased under salinity stress but the GPC increased (Baxter et al 2011 ; Thitisaksakul et al 2015 ), which is consistent with the findings from this study, implying that salinity stress increases the ability of plants to mobilize N in developing seeds at the expense of the carbon sink and source, resulting in less dry matter accumulation. The decrease in GSC might be connected with the lower plant growth rate—a direct consequence of the photosynthetic limitation in plants, which may have indirectly contributed to a reduction in the sink capacity and less starch deposition in the grains.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, ozone (O 3 ) (Piikki et al 2008 ; Zheng et al 2013 ) and heat (Farooq et al 2011 ) stresses have been shown to increase the GPC in wheat, while the study conducted by Fuhrer et al ( 1990 ) revealed that O 3 stress decreases the GSC. In rice, the GSC decreased under salinity stress but the GPC increased (Baxter et al 2011 ; Thitisaksakul et al 2015 ), which is consistent with the findings from this study, implying that salinity stress increases the ability of plants to mobilize N in developing seeds at the expense of the carbon sink and source, resulting in less dry matter accumulation. The decrease in GSC might be connected with the lower plant growth rate—a direct consequence of the photosynthetic limitation in plants, which may have indirectly contributed to a reduction in the sink capacity and less starch deposition in the grains.…”
Section: Discussionsupporting
confidence: 90%
“…A 8% (w/v) starch slurry was analyzed on an AR1000‐N Rheometry (TA Instrument, New Castle, DE), following the method described by Thitisaksakul et al . RVA readings were done in triplicate for each biological replicate.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, grain quality parameters of important cereal crops, such as wheat (Triticum durum Desf. and Triticum aestivum L.) [28][29][30], rice (Oryza sativa L.) [31], or corn (Zea mays L.) [32], could be improved by applying salinity, depending on the specific conditions and cultivars. However, decreased wheat [30,33] or rice [34] grain quality in addition to yield decline under salt stress conditions has also been reported.…”
Section: Soil Salinity and Plant Interactionsmentioning
confidence: 99%